2014
DOI: 10.1002/2014tc003576
|View full text |Cite
|
Sign up to set email alerts
|

Seismotectonics of the Pamir

Abstract: Based on a 2 year seismic record from a local network, we characterize the deformation of the seismogenic crust of the Pamir in the northwestern part of the India-Asia collision zone. We located more than 6000 upper crustal earthquakes in a regional 3-D velocity model. For 132 of these events, we determined source mechanisms, mostly through full waveform moment tensor inversion of locally and regionally recorded seismograms. We also produced a new and comprehensive neotectonic map of the Pamir, which we relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
294
2
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(322 citation statements)
references
References 88 publications
(176 reference statements)
19
294
2
1
Order By: Relevance
“…However, the strong extensional component of the focal mechanisms are opposite what would be expected for a left bend in the dextral Karakoram fault, and we interpret them to be related to westward extensional collapse of the Pamir (i.e. Schurr et al, 2014). end of the Kongur Shan fault system (Fig.…”
Section: Late Quaternary Slip History Of the Northern Karakoram Faultmentioning
confidence: 54%
See 2 more Smart Citations
“…However, the strong extensional component of the focal mechanisms are opposite what would be expected for a left bend in the dextral Karakoram fault, and we interpret them to be related to westward extensional collapse of the Pamir (i.e. Schurr et al, 2014). end of the Kongur Shan fault system (Fig.…”
Section: Late Quaternary Slip History Of the Northern Karakoram Faultmentioning
confidence: 54%
“…1C) (Ischuk et al, 2013;Wang et al, 2001;Zhang et al, 2004). Further, recent detailed work on the seismicity of the Pamir suggests the eastern portion of the Pamir are experiencing little internal deformation (Schurr et al, 2014). One complication is the observed seismicity along the dextral Aksu-Murghab fault zone in the southeast Pamir (Strecker et al, 1995), where two earthquakes yielded strongly oblique dextral-normal focal mechanisms (Schurr et al, 2014).…”
Section: Late Quaternary Slip History Of the Northern Karakoram Faultmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such a far-field response should be expressed as more direct and local driving force. Sobel et al (2013) attributed the Oligo-Miocene boundary thermochronological ages observed in the margins of southwest Tarim basin to the initial underthrusting of the Tarim block beneath the surrounding orogens, which has been testified by geophysical data in the sTS, Pamir and West Kunlun (e.g., Matte et al, 1996;Gao et al, 2000;Kao et al, 2001;Li et al, 2001;Buslov et al, 2007;Li et al, 2012;Jiang et al, 2004;Wittlinger et al, 2004;Schurr et al, 2014;Sippl et al, 2013aSippl et al, , 2013bSchneider et al, 2013). The widespread thermochronological records of this episode in West Kunlun and also sTS (Hendrix et al, 1994;Yang et al, 2003;Du and Wang, 2007;Wang and Du, 2009;Chang et al, 2012;Sobel and Dumitru, 1997;Sobel et al, 2006;Chen et al, 2008;De Grave et al, 2012;Macaulay et al, 2014) imply that the onset of underthrusting of the Tarim block during the this episode was not only limited in southwest margin of the Tarim basin, but can also take place in the south and north margins of the basin.…”
Section: Tectonic Implicationsmentioning
confidence: 98%
“…(2) The Alai region with the Alai Valley (see Figure 1; SW Tien Shan), the Alai range north of the Alai Valley, and the Trans Alai Range south of the Alai Valley, which are all located to the south of the Fergana basin. The Trans Alai is already part of the Pamir mountains (Schurr et al 2014). (3) The Naryn basin, another major intermontane basin within the Tien Shan ranges, is located east of the study area.…”
Section: Tectonic Settingmentioning
confidence: 99%